Study about Classified Indian Reclaimed Asphalt Pavement (RAP): Aggregate Impact and Abrasion Value Approach - Anil Kumar Yadava; Syed Aqeel Ahmad (Technological Innovation in Engineering Research Vol. 4, 2022)
Recycling of bituminous pavement refers to the reuse of existing damaged bituminous pavement material in the building and maintenance of flexible pavement. Reclaimed asphalt pavement(RAP) is degraded pavement material that has been removed and reconditioned before being repurposed. In India, multiple types of bituminous layers are used during the building of flexible pavements, depending on the CBR of the sub-grade and the traffic count such as CVPD of the road stretch. Reclaimed Asphalt Pavement can be classed into numerous groups depending on the type of bituminous layer used, such as PC Seal Coat, Bituminous Macadam (BM), Dense Grade Bituminous Macadam (DBM), Semi Dense Bituminous Concrete (SDBC), or Bituminous Concrete (BC). These categorised RAP groups materials will have diverse features, such as Rap aggregates and Recovered bitumen from various RAP groups. The Aggregate Impact Value (AIV) and Aggregate Abrasion Value (AAV) of RAP aggregates grouped in distinct groups were used in this study to characterize RAP. The findings will be compared to the standard AIV and AAV values necessary for bituminous construction to determine whether RAP aggregates are suitable for use in bituminous mixtures.